Issue Information. Issue 2 (3rd June 2016) - Unknown
Abstract : The current issue opens with an examination of how the target's gender, as a primary context factor, influences the trusting behavior of individuals in an experimental study. This is followed by an investigation of how a an instrument for measuring social desirability, the Marlowe‐Crowne Social Desirability Scale, performs in English and Mandarin Chinese versions in a Malaysian context. Another popular instrument, the Tangney Self‐Control Scale, is the focus of an examination of the psychometric properties and suitability of newly translated full and brief Chinese versions. Next is a study of the reliability and validity of the International Affective Picture System, a standardized tool widely used in psychological studies to induce emotions, with a sample of Chinese older adults. This is followed by a review article, a meta‐analysis on the relationship between positive affect and mortality risk in older adults, based on 22 studies conducted between 1992 and 2013 that were selected from a preliminary screening of over 900 articles. The issue closes with an announcement of a new category of submissions, Short Communications, to be initiated later this year as a format intended to promote concept‐oriented rather than data‐driven submissions, with a quick turnaround time from submission to publication.